2018
DOI: 10.1029/2017jd028246
|View full text |Cite
|
Sign up to set email alerts
|

Spring Land Surface and Subsurface Temperature Anomalies and Subsequent Downstream Late Spring‐Summer Droughts/Floods in North America and East Asia

Abstract: Sea surface temperature (SST) variability has been shown to have predictive value for land precipitation, although SSTs are unable to fully predict intraseasonal to interannual hydrologic extremes. The possible remote effects of large‐scale land surface temperature (LST) and subsurface temperature (SUBT) anomalies in geographical areas upstream and closer to the areas of drought/flood have largely been ignored. Here evidence from climate observations and model simulations addresses these effects. Evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
92
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(114 citation statements)
references
References 70 publications
12
92
1
Order By: Relevance
“…Our MCA analyses show that the spring LST is significantly coupled with the regional snow cover in preceding months. This provides observational evidence to the conjecture in Xue et al () that a temporally filtered response to snow anomalies is preserved in the LST memory, with the latter a more effective predictor to drought and flood events. The TP region snow cover can further originate back to the anomalous atmospheric circulation in middle and high latitudes in February, suggesting that the February anomalous circulation, through the resultant anomalies in snowfall in late winter and snow cover in early spring in TP region, can eventually lead to large‐scale anomalies in LST in spring time.…”
Section: Summary and Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our MCA analyses show that the spring LST is significantly coupled with the regional snow cover in preceding months. This provides observational evidence to the conjecture in Xue et al () that a temporally filtered response to snow anomalies is preserved in the LST memory, with the latter a more effective predictor to drought and flood events. The TP region snow cover can further originate back to the anomalous atmospheric circulation in middle and high latitudes in February, suggesting that the February anomalous circulation, through the resultant anomalies in snowfall in late winter and snow cover in early spring in TP region, can eventually lead to large‐scale anomalies in LST in spring time.…”
Section: Summary and Discussionsupporting
confidence: 79%
“…However, the subsequent studies showed that the effects of the snow cover on summer precipitation are highly variable (e.g., Bamzai & Shukla, 1999;Liu & Yanai, 2002;Wu & Qian, 2003;Xiao & Duan, 2016;Xue et al, 2012), suggesting the difficulty of using snow in TP directly as a predictor for droughts and flood events. Studies by Xue, Oaida, et al, (2016) and Xue et al (2018) therefore conjectured that a temporally filtered response to the snow anomalies may be preserved in the LST and found that, in both North America and East Asia, the springtime large-scale LST anomalies all significantly affect the early summer precipitation in its downstream region. Their observational analysis show that the connections between the LST and its downstream summer precipitation are as significant as the well-known SST-precipitation connections.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, during May 2015, Southern Great Plains and several adjacent cities (hereafter referred to as SGP) saw one of their wettest Mays on record, which was neither fully predicted nor anticipated. This flood event made headlines in many media outlets, while the property damage in Houston alone was estimated to more than $40 million (Wang et al 2015;Mekonnen et al 2016;Xue et al 2018). Despite considerable progress in understanding processes controlling the US seasonal/intraseasonal rainfall variability (see review by Koster et al 2017, and paper cited therein), accurately predicting these extreme events in models still remains a challenge .…”
Section: Introductionmentioning
confidence: 99%
“…• For about 2/3 land areas, JJA precipitation is more sensitive to local ET than nonlocal ET in a point-to-point sense • For about 1/5 land areas, JJA precipitation is on average sensitive to ET of more than 1,000 km away • Remote sensitivities are much smaller than local sensitivities but could be large when combined and may be useful for some regions weather and climate through winds or atmospheric waves (Koster et al, 2016;Schumacher et al, 2019;Teng et al, 2019;Xue et al, 2018) or direct moisture transport (e.g., Alter et al, 2015;Herrera-Estrada et al, 2019;Lo & Famiglietti, 2013;Wei et al, 2013). Almost all these works are case studies, and a complete global picture is still elusive.…”
Section: 1029/2019gl085613mentioning
confidence: 99%